2022
DOI: 10.3390/ijms23031011
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Transplantation and Cell-Free Treatment for Periodontal Regeneration

Abstract: Increasing attention has been paid to cell-based medicines. Many in vivo and in vitro studies have demonstrated the efficacy of stem cell transplantation for the regeneration of periodontal tissues over the past 20 years. Although positive evidence has accumulated regarding periodontal regeneration using stem cells, the exact mechanism of tissue regeneration is still largely unknown. This review outlines the practicality and emerging problems of stem cell transplantation therapy for periodontal regeneration. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…DFSCs have showed considerable advantages in promoting periodontal tissue regeneration [ 16 , 34 , 58 ]. However, there are still many difficulties in the clinical application of stem cells, especially possible utility, safety, and ethical issues [ 59 ]. Molecular drugs may be relatively more convenient, safe, and stable [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…DFSCs have showed considerable advantages in promoting periodontal tissue regeneration [ 16 , 34 , 58 ]. However, there are still many difficulties in the clinical application of stem cells, especially possible utility, safety, and ethical issues [ 59 ]. Molecular drugs may be relatively more convenient, safe, and stable [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various stem cell transplantation techniques have been used, such as direct injection of stem cells grown in culture medium at the site of the periodontal defect [36], using a sponge impregnated with stem cells, or injecting the culture medium with enriched stem cells [79]. The use of carriers to implant stem cells in the place of a periodontal defect reduces the viability and proliferation of these cells; therefore, the direct injection method is preferred [80].…”
Section: Induced Pluripotent Stem Cells (Ipscs)mentioning
confidence: 99%
“…Since then, numerous studies have shown that MSCs can be cultured, and MSCs can differentiate beyond mesenchymal lineages, such as bone, cartilage, and fat, to mesodermal tissues, including muscle, in vitro and ex vivo . Several preclinical studies and clinical trials have also shown the efficacy of MSC transplantation [23] , [24] , [25] . However, unlike hematopoietic stem cells, which are more strictly defined and can form the entire hematopoietic system by single cells, MSCs are heterogeneous, and single cells do not form entire tissues.…”
Section: Stem Cell Populations In Periodontal Tissuementioning
confidence: 99%